KETERKAITAN TEORI SIKLUS HIDUP KEUANGAN DALAM KEBIJAKAN DIVIDEN: STUDI PADA SEKTOR EKONOMI YANG LISTING DI BEI - Meuthia Hapsari Imayanti (ETIKONOMI, 2013)
The purpose of this study is to analyze the linkage of financial life cycle theory to dividend policy. This study is using control variables consisting of Leverage, Return on Asset, Size and Asset Growth Rate. The data used in this study are the data in the sectors of primary and secondary market at Indonesia Capital Market (BEI). This study uses Binary Logistic Method. The factors that affect Dividend Policy in developed stock market seem to apply for this emerging market. Factor such as changes Size and ROA have positive effects on the probability of changes dividend. But, only Size has negative effects on the probability of omitting dividends. This research found that Financial Life Cycle difficult to seen in Indonesia, especially when the crisis is going onDOI: 10.15408/etk.v12i1.1902